(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Alumina has unique textural properties and functionalized surface. The single or multi-treatments of alumina with calcination and alkali metal treatment (NaCl) are of prime one importance not only for determining the structure, textural and surface chemistry of the phase but also to understand how modification is related to the changes in these properties and also to the change in its performance as solid stationary phase. Thermodynamic parameters (Î”H, Î”G and Î”S) were determined using n-hexane as a probe in order to show the adsorbate-adsorbent interaction. It was observed that the non-polar solutes could be separated independent of the reactivity and porosity of the alumina surfaces. Alkali metal modification of the calciened alumina is a selective stationary phase for eluting natural gas sample exhibiting good separation.